Using dietary additives to improve palatability of diets containing single-cell protein from methanotrophic bacteria in yellowtail kingfish (Seriola lalandi) diets - LW Pilmer; LD Woolley; AJ Lymbery; Michael Salini; GJ Partridge (2022)
Using dietary additives to improve palatability of diets containing single-cell protein from methanotrophic bacteria in yellowtail kingfish (Seriola lalandi) diets